MODIFIKASI PATI TALAS DENGAN ASETILASI MENGGUNAKAN ASAM ASETAT - Mochamad Adi Saputro; Arizal Kurniawan; Diah Susetyo Retnowati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
In Indonesia, taro is consumed as a staple food and food additives. Taro contains a high carbohydrates, proteins, fats and vitamins. Goverment continuous to support taro as non food material, yet it has a potential to be developed. Natural starch (native) has several problems associated with retrogradasi, stability, and low resistance paste. It’s became a reason for the starch modify, to get suitable properties for certain applications. Modification can be done by chemically, physically or enzymatically. One of chemically modified starch is acetylation method. One Hundredgrams of starch added to the acetic acid solution and stirred at certain temperature for 30 minutes. The resulting starch is filtered and then dried at 50oC for 24 hours. Filtrate is titrated with 0.5 N NaOH to know remaining acetic acid. Starch which has dried then milled to obtain a fine powder then the swelling power and solubility were analyzed.Temperature had no effect in the acetylation process of taro starch.  The best ratio volume acetic acid-water obtained for food material is 4.5 ml /250 ml at 35oC and the